KLASIFIKASI KALIMAT PADA BERITA OLAHRAGA SECARA OTOMATIS MENGGUNAKAN METODE ARTIFICIAL NEURAL NETWORK - Asep Saepul Ridwan; Yulison H Chrisnanto; Ridwan Ilyas (J-Icon : Jurnal Komputer dan Informatika, 2021)
Sports news is of great interest to today's society. This is because sports have grown into entertainment. There is a lot of sports news today that covers a wide range of sports, from branches that use the ball as objects for games like football, to sports in automotive race like formula 1. Beyond that, the substance of the sports news itself is as diverse as the news of managerial from a sports club, results matches, player injuries, et cetera. Surely such a thing would be difficult. The network wants one in the field of discussion in the news. Overlap data occurs in the sports news document because it mixes one sentence data with the other. Some of the content in the sports news is about managerial, players, schedules, previews, reviews, standings, statistics, champions, etc. Becomes a problem when the reader wants a topic on the news that focuses on one particular discussion. This study has built a book on sentence classification meaning Artificial Neural Network (ANN) with a method of learning Backpropagation. The feature used is the frequency of the occurrence of a term in the corresponding sentence and the calculating result of a distributed term. The testing of our proposed methods shows an accuracy of 99% to best results on training data and 57% on test data.